The quality of the content of the science curriculum for the fifth and sixth grades from the point of view of teachers and mentors in Lattakia Governorate - مسلم, سناء; منال سلطان ,; منال سلطان , (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of this research is to determine the level of quality of the content of the science curriculum for the fifth and sixth grades from the point of view of teachers and mentors in Lattakia Governorate, and the impact of the variables (job, educational qualification, and number of years of experience) on that. The quality of the content of the curriculum contained in (Guideline for Quality Control of Educational Curricula, 2020) issued by the Ministry of Education in the Syrian Arab Republic. Lattakia and the research reached the following results: - The level of content translation of the science curriculum standards for the fifth and sixth grades from the point of view of teachers and mentors in Lattakia governorate was high. -The level of choosing the content of the science curriculum for the fifth and sixth grades and organizing it according to clear bases from the point of view of teachers and mentors in Lattakia governorate was high. -The level of quality of the content of the science curriculum for the fifth and sixth grades with the personal and societal dimensions in the lives of learners from the point of view of teachers and mentors in Lattakia governorate is average. - There are statistically significant differences between the mean scores of the educational mentors' and teachers' responses regarding the quality of the content of the science curriculum for the fifth and sixth grades according to the job variable in favor of the educational mentors. - There are statistically significant differences between the average scores of the responses of the educational counselors and teachers regarding the quality of the content of the science curriculum for the fifth and sixth grades according to the scientific qualification variable in favor of those with an educational qualification diploma. - There are no statistically significant differences between the mean scores of the responses of the educational counselors and teachers regarding the quality of the content of the science curriculum for the fifth and sixth grades, according to the variable of the number of years of experience.